GEOMETRY OPTIMIZATION OF WATER-JET MACHINE CUTTING HEAD USING FINITE ELEMENT METHOD - Szczepanik, Maciej (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2014)
The article presents optimization process of water-jet cutting head geometry using ANSYS Workbench software. The aim of study was to examine influence of specific dimensions on output abrasive stream flow parameters. Statistical analysis of the results will help to reduce the complexity of the model in the later studies by omitting irrelevant parameters.